Green infrastructure for urban resilience: a trait‐based framework. Issue 4 (16th December 2021) - Reynolds, Heather L; Mincey, Sarah K; Montoya, Robert D; Hamlin, Samantha; Sullivan, Abigail; Thapa, Bhuwan; Wilson, Jeffrey; Rosing, Howard; Jarzen, Joseph; Grove, J Morgan
Abstract : Urban areas around the world are increasingly turning to green infrastructure to promote resilience to climate change. Core traits of resilient systems have emerged from diverse disciplines. Here, we draw from existing literature on these core traits to elaborate an explicitly social–ecological systems (SES) and resilience trait‐based framework for operationalizing urban resilience through green infrastructure. We identify social and ecological dimensions of core resilience traits, cover methodological aspects of creating SES‐ and resilience‐based spatial inventories of urban green infrastructure, and discuss how this framework helps to promote systems‐based planning. We demonstrate the application of the framework to several real‐world cases and identify fruitful research directions.